Measurement of large strain properties in calf muscles in vivo using magnetic resonance elastography and spatial modulation of magnetization. (19th April 2018) - Tan, Kristy; Jugé, Lauriane; Hatt, Alice; Cheng, Shaokoon; Bilston, Lynne E.
Abstract : It is important to measure the large deformation properties of skeletal muscle in vivo in order to understand and model movement and the force‐producing capabilities of muscle. As muscle properties are non‐linear, an understanding of how the deformation state affects the measured shear moduli is also useful for clinical applications of magnetic resonance elastography (MRE) to muscle disorders. MRE has so far only been used to measure the linear viscoelastic (small strain) properties of muscles. This study aims to measure the shear moduli of human calf muscles under varying degrees of strain using MRE. Nine healthy adults (four males; age range, 25–38 years) were recruited, and the storage modulus G ′ was measured at three ankle angle positions: P0 (neutral), P15 (15° plantarflexed) and P30 (30° plantarflexed). Spatial modulation of magnetization (SPAMM) was used to measure the strain in the calf associated with the ankle rotations between P0 to P15 and P0 to P30. SPAMM results showed that, with plantarflexion, there was a shortening of the medial gastrocnemius and soleus muscles, which resulted in an expansion of both muscles in the transverse direction. Strains for each ankle rotation were in the range 3–9% (in compression). MRE results showed that this shortening during plantarflexion resulted in a mean decrease in G ′ in the medial gastrocnemius ( p = 0.013, linear mixed model), but not in the soleus ( p = 0.47). This study showed that MRE is a viable technique for the measurement of large strain deformation properties in vivo in soft tissues by inducing physiological strain within the muscle during imaging. Abstract : This study showed that magnetic resonance elastography is a viable technique to measure large strain deformation properties in vivo in calf muscles by inducing physiological strains within the muscle with plantarflexion. The results showed that, with plantarflexion, there was a shortening of the gastrocnemius and soleus muscles along their length ( y ‐direction) and that muscle shear moduli in the gastrocnemius decreased as it shortened. Strains induced by plantarflexion were in the range 3–9% (in compression), as quantified with spatial modulation of magnetization (SPAMM) methods.